An Analytical Study of Public Mind of Phra Narai Lopburi Rotary Members According To Buddhist Peaceful Means - Saengwatanarerk, Chittra; Dhammahaso, Phramaha Hansa; Wattanapradith, Khantong (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
This thesis has three objectives which are (1) to study the volunteer working concept of members in Phra Narai Lopburi, (2) to study the bases of sympathy in Theravada Buddhism scriptures and (3) to analytically study the volunteer working of Rotary members in Phra Narai Lopburi. The research methodology of Qualitative Field Research has been used by studying from the documents and an in-depth interview. The results of this research are:- Phra Narai Lopburi Rotary Club has 4 visions in its working following the international Rotary which are Truth Emphasis means an establishment based on the honesty thought with the actual information and fact, but without the induction of the organization to serve or seek for personal interests. Impartial Adherence means an upholding of justice, equality and respect by containing justice, support and nurture. Friendship Leading means a building of good interpersonal relationship with an act of friendliness. Good for All Parties means a determination to build happiness for the mankind. The research results were found that the bases of sympathy in Buddhism scriptures were the Dhamma principle that volunteer workers had to bear in mind. It consisted of 4 aspects which were Giving means a donation of utensils, appliances and knowledge. Kindly speech means the use of polite and sweet words, with humble manners. Rendering Services means a useful conduct to the society without hoping something in returns, with sacrificing physical and mental supports. Participation and behaving oneself properly in all circumstances with even and equal treatment. The volunteer working of Rotary members in Phra Narai Lopburi had a characteristic of goodwill unity within the organization and liaison according to the four bases of sympathy resulting the members to love and bond together. The researcher could decode the lesson from the volunteer working of Rotary members in Phra Narai Lopburi to be a virtue model with dedication of both spirit and strength, Inheritance of the giver’s ideology, giving of love and forgiveness and synchronization of mind and harmonious speech.